The Impact of Empathy on Worldwide Religious Conflict: Insight from The Gaza Situation - Sufya, Dina Haya; Munawwaroh, Lailatul; Deliani, Nurfarida (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
This study aims to examine the effect of empathy on religious conflict, using Gaza as a case study. The method employed was simple regression analysis on a sample of 151 Muslim students aged 18-25 years. This research applied a quantitative approach with a cross-sectional design to analyze the relationship between variables. The results indicate that empathy significantly affects religious conflict, with a coefficient value of sig = .000 (p < .05). These findings suggest that empathy can be one of the factors in reducing tensions between groups in religious contexts. However, this study is limited to a student sample and a single case context, so the results must be generalised cautiously. Future research should expand the demographic scope and consider other socio-cultural factors to gain a more comprehensive understanding. These findings are expected to contribute to developing empathy-based interventions to reduce tensions in religious and social contexts.